Global trends and practice patterns in virtual reality simulation training for ophthalmic surgery: an international survey use of virtual reality simulation training around the world - Dormegny, Lea; Yaïci, Remi; Koestel, Emilia; Dhubhghaill, Sorcha Ní; Ahiwalay, Chetan; Bacchav, Ashish; Bourges, Jean-Louis; Dechriste, Gauthier; Dick, H. Burkhard; Filipe, Helena Prior; Flockerzi, Elias; Gaucher, David; et al. (Scientific reports, 2025)
This global survey investigated the use of virtual reality simulation (VRS) in ophthalmological surgery education. Questionnaires were distributed to authors of publications and directors of centers using VRS for surgical education in ophthalmology, then forwarded to residents and fellows of their team for completion. Out of 1845 questionnaires sent across 36 countries, 170 responses from 26 countries were analyzed, primarily from residents and fellows (75%). Mean access duration to VRS was 3.6 years, often at University Hospitals (43.5%). Notably, 12% of respondents traveled an average of 550 km to access VRS. The EyeSi VR Magic was the most frequently reported simulator (80%, mainly in Europe/North America), followed by HelpMeSee (48%, primarily in Europe/India/Madagascar). In 25 training centers across 12 countries, VRS was a mandatory prerequisite for patient access, functioning as a “surgical license”. A larger number of training centers (49 from 19 countries) favored such mandatory training. Junior surgeons perceived a greater impact of VRS on their surgical practice compared to senior surgeons ( p = 0.032). The study concludes that while VRS holds a significant role in postgraduate ophthalmic surgical training, its access is unequal worldwide. Broader implementation and standardized practices could improve and maintain high educational standards in this field.